Analisis Kebijakan Permendiknas No.70 tahun 2009 Tentang Sekolah Inklusi - Husnul Khotimah (Realita: Jurnal Penelitian dan Kebudayaan Islam, 2019)
This study aims to analyze the implementation of education policies on the existence of inclusive schools contained in the Minister of National Education Regulation Number 70 of 2009. Starting from the gap that arises when children with special needs have education separately from normal children, namely in SLB eventough in Article 31 of the 1945 Constitution state that all citizens without exception have the right to get education. The method used is the Qualitative method with library research studies. The source of the data come from the policy literature and several previous studies related to the inclussion school. Policy analysis theory uses the E.S. Quade theory with the result of research that show that the policies related to inclusive school contain some systematic education implementation which ultimately can realize the principles of Education for all. However, problems arise related to the unpreparedness of school providing inclussion education service which result in learning processes that seem forced and ultimately result learning is not optimal. This requires a new policy from goverment related to te classification of eligible school to carry out inclusive education and minimum IQ standardtation of student so that they are able to follow the learning process to the fullest.